Reaction of dogs' teeth to root canal filling with mineral trioxide aggregate or a glass ionomer sealer - Holland, Roberto [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Bernabé, Pedro Felício Estrada [UNESP]; Dezan Junior, Eloi [UNESP] (Elsevier, 1999)
This study was conducted to observe the reaction of apical tissues of dogs' teeth after root canal filling with gutta-percha and mineral trioxide aggregate (MTA) or a glass ionomer (Ketac-Endo) as a sealer. The root canals were instrumented and filled by the lateral condensation technique with the sealers studied. Animals were killed 6 months later, and the specimens were removed and prepared for histological analysis. Results showed no inflammatory reaction of apical tissue and total closure of the apical foramen of all the teeth sealed with MTA. The teeth sealed with Ketac-Endo showed two cases of partial closure and different degrees of chronic inflammatory reaction. In conclusion, MTA exhibited better biological properties than Ketac-Endo. Copyright © 1999 by The American Association of Endodontists.
Keywords: aluminum derivative; calcium derivative; glass ionomer; Ketac Endo; mineral trioxide aggregate; oxide; root canal filling material; silicate; animal; cementum; comparative study; dog; drug combination; drug effect; periodontium; tooth pulp disease; tooth root; Aluminum Compounds; Animals; Calcium Compounds; Dental Cementum; Dentin, Secondary; Dogs; Drug Combinations; Glass Ionomer Cements; Oxides; Periapical Tissue; Root Canal Filling Materials; Silicates; Tooth Apex